2012
DOI: 10.1097/iae.0b013e318229b220
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Anti–vascular Endothelial Growth Factor Therapy for Choroidal Neovascularization Secondary to Ocular Histoplasmosis Syndrome

Abstract: Long-term intravitreal anti-VEGF therapy with bevacizumab or ranibizumab is beneficial in treatment of choroidal neovascularization in ocular histoplasmosis syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Treatment of CNV is often successful with administration of anti-VEGF agents. [18,19] Our findings are consistent with these management patterns, with most of the anti-VEGF agent use occurring in the CNV group. PDT and corticosteroid use were also observed although with lower frequency compared with anti-VEGF therapy.…”
Section: Plos Onesupporting
confidence: 85%
“…Treatment of CNV is often successful with administration of anti-VEGF agents. [18,19] Our findings are consistent with these management patterns, with most of the anti-VEGF agent use occurring in the CNV group. PDT and corticosteroid use were also observed although with lower frequency compared with anti-VEGF therapy.…”
Section: Plos Onesupporting
confidence: 85%
“…None of the studies mentioned reported serious side effects related to treatment. 12,13,14 In our case, CNV regressed after a total of 5 doses of intravitreal ranibizumab, leaving a subretinal scar.…”
Section: Discussionmentioning
confidence: 52%
“…4 Case reports and case series support the efficacy of anti-VEGF agents in the treatment of CNV secondary to POHS. 4,12,13,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schadlu et al [35] reported that 85% of 28 eyes had stabilized or improvement in vision with intravitreal bevacizumab therapy with approximately 43% eyes gaining three or more lines of vision. It demonstrated that 94% eyes had improved (81%) or stabilized (13%) visual acuity [36]. It demonstrated that 94% eyes had improved (81%) or stabilized (13%) visual acuity [36].…”
Section: Macular Photocoagulation and Submacular Surgerymentioning
confidence: 96%